Pengembangan Aplikasi Perangkat Bergerak Layanan berbasis Lokasi Penghubung Sukarelawan dengan Kegiatan Sukarela - Rahmatsyah Rahmatsyah; Agi Putra Kharisma; Sutrisno Sutrisno (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Volunteers are individuals or groups who carry out an voluntary activity. Volunteering are usually intended to provide a service without making a profit. From a survei of 144 Indonesian over the age of 17, found that 82.2% difficult to register as a volunteer because of a lack of information regarding volunteer activities, 54.2% were hesitent to register as volunteers because of a lack information about volunteerism activities, and 96,5% felt that they needed a platform to connect volunteers with social activities. Therefore an application is made to connect volunteers with voluntary activities. Location-based application that displays a number of voluntary activities to volunteers based on the closest location. From the results of exploring needs, there are two types of actors namely volunteers as a community who want to become volunteers and social organizations as implementing activities. Therefore two applications were developed that represented the behavior of the two actors. The application was developed with the Model-View-ViewModel (MVVM) architecture and data storage using Firebase services with the results of all functional testing successfully implemented and an average of usability test results above 70% which means it can be accepted by the user, and can be operated on the Android operating system with a minimum version of 16 through 29.